INHIBITION OF SELECTIVE AND NON-SELECTIVE SICLOOXYIGENASE ON ANSIOLITIC EFFECTS INDUCED DIAZEPAM IN MICE - Doni Anshar Nuari; Cindra Tri Yuniar; Ahmad Jaidi; Siva Hamdani; Genialita Fadhila (Jurnal Ilmiah Farmako Bahari, 2022)
Stress is the source of many sociological, medical, and economic problems. Moreover, stresses are known as the etiology of several diseases. Prostaglandins and all four receptors affect the brain, even thought to affect behavior. Hence, the inactivation of cyclooxygenase (COX) causes a decrease in levels of prostaglandins that contribute to stress development, thus decreasing the anxiolytic effect of diazepam. This study aims to see the effect of selective and non-selective COX inhibitors decreasing the Anxiolytic effect of diazepam using the EPM (Elevated Plus Maze) method in male white mice; animals were grouped to use Tragakan 2%, Diazepam 0.065 mg/kg BB and Tragakan 2% after an hour, Diazepam 0.065 mg/kg BB and then an hour later gives Ketoprofen 0.65 mg/kg BB for non-selective COX Inhibitor effect group, Diazepam 0.065 mg/kg BW, and then an hour later gives Celecoxib 0.65 mg/kg BB for group use of selective Cox-2 Inhibitor, test parameter in this study is the duration in open arm. Results showing decreased duration on open arm group has given diazepam combination ketoprofen or celecoxib are different P value <0.05 than diazepam only. Decline duration was highest shown by animals given celecoxib, so that could be stated gift selective COX-2 inhibitors bring down the effect of anxiolytic diazepam bigger.